A simple protocol for DNA extraction from dog hairs - Quan, Thai Ke; Tu, Nguyen Van; Hieu, Huynh Van; Cong, Nguyen Thanh; Dung, Tran Hoang (Academia Journal of Biology, 2016)
The Phu Quoc ridgeback dog is a Vietnamese valuable dog breed, which is in study for genetic resource conservation. In previously published studies, the common material for DNA extraction is blood. However, the invasive blood sampling technique is difficult to apply due to either dog’s uncomfortable reaction or the disagreement of the dog owners. For easier in material sampling, a protocol for DNA extraction from dog hairs is proposed using common chemicals such as SDS, proteinase K… Hair roots (1 cm in length) are treated with proteinase K included lysis buffer in 60 minutes. Released DNA in the solution is separated with others by phenol:chloroform mixture, and precipitated in absolute ethanol. Extracted DNA is then dissolved in distilled water and stored at -30 oC. With this protocol, good-quality DNA is extracted and can be used in further studies with PCR, sequencing techniques. The protocol is simple, high sensitive, i.e. can yield DNA from only one hair shaft.